Increased T Cell Plasticity With Dysregulation of Follicular Helper T, Peripheral Helper T, and Treg Cell Responses in Children With Juvenile Idiopathic Arthritis and Down Syndrome–Associated Arthritis. Issue 4 (12th March 2020) - Foley, C.; Floudas, A.; Canavan, M.; Biniecka, M.; MacDermott, E. J.; Veale, D. J.; Mullan, R. H.; Killeen, O. G.; Fearon, U.
Abstract : Objective: Juvenile idiopathic arthritis (JIA) is the most common inflammatory arthritis in children; however, an aggressive, erosive arthritis of little‐known immunologic mechanism occurs 20 times more frequently in children with Down syndrome. This study was undertaken to characterize T cell and B cell polyreactivity, follicular helper T (Tfh) cell, peripheral helper T (Tph) cell, and Treg cell responses, and synovial inflammation in Down syndrome–associated arthritis (DA). Methods: Multiparametric flow cytometric analysis and Simplified Presentation of Incredibly Complex Evaluations (SPICE) software were used to examine peripheral blood B cell populations and T cell cytokine responses in patients with DA, JIA, Down syndrome (trisomy 21 [T21]), and in healthy controls. Tfh and Tph cell frequency and origin, in addition to Treg cell frequency, were also evaluated. Synovial inflammation was assessed by immunohistology. Results: Expansion of IgM‐only memory B cells was demonstrated in DA compared to JIA (mean ± SEM 22.48 ± 3.278 versus 9.011 ± 1.317; P = 0.005), paralleled by decreased frequency of transitional B cells. T cell responses in DA were characterized by marked functional plasticity, as was evident from the increased frequency of polyfunctional CD8+ Th cells ( P < 0.05), CD161+ Th cells ( P < 0.05), and CD8− Th cells ( P < 0.001), and positivity for tumor necrosis factor, interferon‐γ, interleukin‐17A, or granulocyte–macrophage colony‐stimulating factor, compared to all other groups. Significant expansion of CXCR3+CCR6+ (Th1/Th17) Tfh cells ( P = 0.003) and CXCR3+CCR6+ Tph cells ( P = 0.01), paralleled by a decrease in CXCR3−CCR6− (Th2) Tfh cells was observed in DA compared to T21. Treg cells were significantly reduced in DA compared to T21 (mean ± SEM 7.111 ± 0.9518 versus 11.96 ± 1.055 versus; P = 0.0028), with a specific reduction in the naive:memory Treg cell ratio. Marked synovial tissue inflammation and increased T cell and B cell infiltrations were demonstrated in DA compared to JIA. Conclusion: DA is more common and more aggressive than JIA. It is characterized by increased polyreactive Th, Tfh, and Tph cell responses, reduced Treg cell frequency, and evidence of increased synovial inflammation, all of which are potentially distinct from JIA and T21.